2010
DOI: 10.1002/jcb.22558
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses constitutive activation of STAT‐3 by up‐regulating protein inhibitor of activated STAT‐3 (PIAS‐3) in ovarian and endometrial cancer cells

Abstract: Signal transducer and activator of transcription-3 (STAT-3) is constitutively activated in ovarian and endometrial cancers and is implicated in uncontrolled cell growth. Thus, its disruption could be an effective approach to control tumorigenesis. Curcumin is a dihydroxyphenolic compound, with proven anti-cancer efficacy in various cancer models. We examined the anti-tumor mechanism of curcumin on STAT-3 and on the negative regulators of STAT-3, including suppressors of cytokine signaling proteins (SOCS-1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 45 publications
(57 reference statements)
5
78
0
Order By: Relevance
“…1h). These results are very similar to those of curcumin that inhibits Stat3 phosphorylation and decreases SOCS-3 expression in several cancer cell lines (2).…”
supporting
confidence: 84%
“…1h). These results are very similar to those of curcumin that inhibits Stat3 phosphorylation and decreases SOCS-3 expression in several cancer cell lines (2).…”
supporting
confidence: 84%
“…High levels of expression were observed more commonly in those histotypes with aggressive biologic behaviour (undifferentiated, clear cell, and serous carcinomas) than in those histotypes with less aggressive behaviour (mucinous and endometrioid carcinomas). Results from a recent study (Saydmohammed et al, 2010) confirm that IL-6 secretion increases during malignant progression of ovarian epithelial cells and found that IL-6 expression levels are not always correlated with the expression or subcellular location of pSTAT3 in ovarian carcinoma, supporting the finding that IL-6 is involved in other signalling pathways, independent of STAT3. Moreover, given the observations that cancer cells can constitutively express STAT3 in the absence of stimulation by any known ligand and that expression of STAT3 is higher in ovarian carcinoma than in normal ovarian tissue, it is possible to speculate that the constitutive activation of STAT3 in ovarian cancer cells could be because of aberrant EGFR signalling.…”
Section: Proinflammatory Cytokines In the Progression Of Eocmentioning
confidence: 77%
“…Treatment of ovarian cancer cells with curcumin induced a dose-and time-dependent decrease of constitutive IL-6 expression and IL-6-induced STAT-3 phosphorylation, which is associated with decreased cell viability and increased cleavage of caspase-3. Moreover, curcumin suppresses JAK-STAT signalling also via activation of PIAS-3, thus attenuating STAT-3 phosphorylation and tumour cell growth (Saydmohammed et al, 2010). The activity of curcumin on STAT3 is also mediated by its ability to inhibit lysophosphatidic acid (LPA) which is a biolipid that stimulates tumour cell invasion and metastasis by inducing phosphorylation of STAT3 as well as IL-6 and IL-8 secretion, which in turn results in STAT3 phosphorylation.…”
Section: Inflammation and Possible Therapeutic Implicationsmentioning
confidence: 99%
“…Moreover, it decreases cell growth via inactivation of NF-κB, preventing DNA binding, nuclear translocation, and p65 phosphorylation. Curcumin also suppresses activation of STAT-3 as indicated by decreased phosphorylation and inhibition of JAK1 phosphorylation (Rajasingh et al 2006, Saydmohammed, Joseph and Syed 2010, Bill et al 2010. Moreover, curcumin induces expression of peroxisome proliferator activated receptor gamma and upregulates death receptors, DR4 and DR5.…”
Section: Potential Chemo Preventative Agentsmentioning
confidence: 99%